Limelight Larry - Hodgkinson, Leigh (Tiger Tales, 2011)
A peacock called Limelight Larry wants to be the star of the book named for him. But soon other animals are cluttering the pages. When the star finally has his moment in the spotlight, what has happened to all his friends?